Relationship between tree height and diameter at breast height for a 16-Year old stand of Hopea Kerangasensis in Sarawak - Mohamad Kasim, Mohamad Roslan; Tee, Wei Ping (2009)
Information on tree height and diameter at breast height (DBH) are important for estimating growth in the future. A study was undertaken to develop a relationship model between height and DBH of Hopea kerangasensis which was planted in an experimental plot of UPM Bintulu Campus, Sarawak. The relationship between tree height and DBH can be depicted in a form of power function model, H=75.519 DBH1.009, with more than 91% of the variation in tree height can be explained by DBH. Validation process also showed that there was no differences between modeling and validation data (p value=0.563), meaning that the model is valid.